Remote intelligent test method and application of relay protection of smart substation based on autonomous controllable technology - MEN Qiang; LIU Tao; ZHANG Jun; WU Yuanyuan; GAO Kangping (Diance yu yibiao)
Aiming at the problems that the verification time of relay protection devices in smart substations is much longer than the planned power outage time, the workload of verification is large, and the training period of related technical personnel is long, this paper designs a remote intelligent test method for relay protection of smart substations based on autonomous controllable technology. The overall architecture and network architecture of the system are given. Without changing the original network and configuration in the station, one or more dedicated in-station test terminals are deployed to access the process layer and station control layer. The DL/T 860 protocol rules, complex event processing algorithms and alarm correlation analysis engine mechanism process the alarm information generated during the action of relay protection, and propose the remote intelligent simulation test process of relay protection, "one-click" protection simulation test technology and the remote testing technology and method of protection configuring parameters. The correctness of sampling and the integrity of the secondary circuit are verified by using the remote intelligent test method of relay protection of smart substation.